Dialog Ekoteologis Katolik-Islam: Studi Komparatif atas Ensiklik Laudato Si’ Paus Fransiskus dan Konsep Amanah terhadap Alam dalam Islam - Senda, Siprianus Soleman; Sie, Fladimir; Minggu, Yulianus; Raja Mau, Paternus; Ergon, Isfilus; S. Senda, Siprianus; Yohanes Vianey, Watu; Naif, Oktovianus (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2025)
The global ecological crisis calls for deeper interreligious reflection on humanity’s relationship with creation. The Catholic Church, through Pope Francis’ encyclical Laudato Si’, and Islam, through its doctrine of amanah (trusteeship) toward nature, both affirm humanity’s moral responsibility as stewards of creation. Yet, in social and religious practices, these ecological values are often overlooked due to dominant anthropocentric and exploitative paradigms. This study proposes an eco-theological dialogue framework that positions environmental theology as an ethical meeting ground between Catholic and Islamic traditions. Using a qualitative comparative textual analysis of Laudato Si’ and Islamic classical and contemporary sources on amanah, the study finds a profound convergence: the Earth is a divine trust that must be cared for with love, justice, and spiritual responsibility. Both traditions reject environmental exploitation and advocate for faith-based ecological conversion. This dialogue thus provides an ethical foundation for interreligious collaboration toward integral ecology and peace with creation. Keywords: ecotheology, eco-theological dialogue, Laudato Si’, Amanah